Pengaruh Model Self Regulated Learning Terhadap Keaktifan Belajar dan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran IPS Kelas VIII SMPN 1 Sumbergempol - Era Safira Prilamsyah; Larasati Widoningtyas (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
This research is based on the by the low learning activity, students tend to be passive during the learning process and students are not used to thinking more deeply, the ability to understand and respond to questions is still low. This study aims to determine the effect of the Self-Regulated Learning model on learning activity and critical thinking skills of VIII students of SMPN 1 Sumbergempol. This study uses a quantitativ approch with a quasi-experimental type with a pretest-posttest control group design. The research sample was selected using a purposive sampling technique. Data collection was carried out using a learning activity questionnaire and a critical thinking ability test. Data analysis used prerequisite tests, namely normality and homogeneity tests, and hypothesis testing, namely using Independent Sample T-Tests and MANOVA tests. The results of the study showed that the application of the Self-Regulated Learning model did not have a significant effect on learning activity, but had a significant effect on students' critical thinking skills. The implication of this study is that the Self-Regulated Learning model can be used as an alternative learning strategy to improve students' critical thinking skills and still needs to be adjusted to student characteristics, and can be combined with other learning strategies for more optimal implementation.